1996
DOI: 10.1007/bfb0046967
|View full text |Cite
|
Sign up to set email alerts
|

Point-based elastic registration of medical image data using approximating thin-plate splines

Abstract: Abstract. We consider elastic registration of medical image data based on thin-plate splines using a set of corresponding anatomical point landmarks. Previous work on this topic has concentrated on using interpolation schemes. Such s c hemes force the corresponding landmarks to exactly match each other and assume that the landmark positions are known exactly. H o wever, in real applications the localization of landmarks is always prone to some error. Therefore, to take i n to account these localization errors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 15 publications
0
84
0
Order By: Relevance
“…Two different spline families that have been used extensively in the literature to model 3D transformations are thin-plate splines and B-splines. Kim et al [55] and Rohr et al [56] have reported methods based on thin-plate splines to perform deformable image registration. However, one major drawback of thin-plate splines is that they have infinite support.…”
Section: Deformable Modelsmentioning
confidence: 99%
“…Two different spline families that have been used extensively in the literature to model 3D transformations are thin-plate splines and B-splines. Kim et al [55] and Rohr et al [56] have reported methods based on thin-plate splines to perform deformable image registration. However, one major drawback of thin-plate splines is that they have infinite support.…”
Section: Deformable Modelsmentioning
confidence: 99%
“…Methods can be divided in two classes : sparse and dense. In the first one, deformation is evaluated from a few set of control points with a deformation model such as thin-plate spline [7,8]. In the second one, a displacement vector is computed at each point leading to a dense deformation field.…”
Section: State Of the Artmentioning
confidence: 99%
“…In this way, features with low-levels of saliency influence the internal deformation to a lesser extent. The implementation involves minimizing the functional [16]: (5) where λ is the regularisation parameter that controls the amount of smoothness in the deformation and σ i 2 are the uncertainty terms.…”
Section: Final Registrationmentioning
confidence: 99%